Clinical, Molecular, and Histopathological Aspect of Primary Biliary Cholangitis - Flora Dameria; Marini Stephanie; Ria Kodariah; Diah Rini Handjari; Ening Krisnuhoni; Nur Rahadiani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Primary biliary cholangitis (PBC), previously known as primary biliary cirrhosis, is an autoimmune liver disease which tends to be chronic and progressive in nature that is marked by the presence of cholangitis and small size biliary duct destruction which may cause cirrhosis or even liver failure. PBC incidence increases because PBC can now be diagnosed earlier and is due to the increasing survival rate of PBC patients. Diagnosis of PBC can be confirmed in asymptomatic state if in the indirect immunofluorescence (IIF) examination revealed AMA positive, and there is an abnormal liver function. Etiopathogenesis of PBC is multifactorial which involves genetic and environmental factors. Genetic factors which contribute to the incidence of PBC are HLA and non-HLA genes, while in the environmental factors, the triggering factors of PBC are bacterial infection and xenobiotic. Interaction of these factors causes the development of E2 subunit pyruvate dehydrogenase complex (PDC-E2) and antimitochondrial antibody (AMA) as the causing autoantigen of biliary duct desctruction in PBC, mediated by the immune system. PBC stage is divided into minimal, mild, moderate and severe. Ursodeoxycholic acid (UDCA) is the first line therapy for PBC, while obeticholic acid (OCA) and fibrate is used as the second line. Liver transplantation is the definitive therapy for PBC where disease progresses into the advanced stage, although the patients have received medical treatment.